Citizenship, Democracy and Belonging in Suburban Britain Making the local - Jeevendrampillai, David (UCL Press, 2021)
A study of the conditions of being a citizen, belonging and democracy in suburban Britain, this book focuses on understanding how a community takes on the social responsibility and pressures of being a good citizen through what they call 'stupid' events, festivals and parades. Building a community is perceived to be an important and necessary act to enable resilience against the perceived threats of neoliberal socio-economic life such as isolation, selfishness and loss of community. Citizenship, Democracy and Belonging in Suburban Britain explores how authoritative knowledge is developed, maintained and deployed by this group as they encounter other 'social projects', such as the local council planning committee or academic projects researching participation in urban planning. The activists, who call themselves the 'Seething Villagers', model their community activity on the mythical ancient village of Seething where moral tales of how to work together, love others and be a community are laid out in the Seething Tales. These tales include Seething 'facts' such as the fact that the ancient Mountain of Seething was destroyed by a giant. The assertion of fact is central to the mechanisms of play and the refusal of expertise at the heart of the Seething community. The book also stands as a reflexive critique on anthropological practice, as the author examines their role in mobilising knowledge and speaking on behalf of others Citizenship, Democracy and Belonging in Suburban Britain is of interest to anthropologists, urban studies scholars, geographers and those interested in the notions of democracy, inclusion, citizenship and anthropological practice.